Cell cycle-independent phospho-regulation of Fkh2 during hyphal growth regulates Candida albicans pathogenesis. - Jamie A Greig; Ian M Sudbery; Jonathan P Richardson; Julian R Naglik; Yue Wang; Peter E Sudbery (PLoS Pathogens)
The opportunistic human fungal pathogen, Candida albicans, undergoes morphological and transcriptional adaptation in the switch from commensalism to pathogenicity. Although previous gene-knockout studies have identified many factors involved in this transformation, it remains unclear how these factors are regulated to coordinate the switch. Investigating morphogenetic control by post-translational phosphorylation has generated important regulatory insights into this process, especially focusing on coordinated control by the cyclin-dependent kinase Cdc28. Here we have identified the Fkh2 transcription factor as a regulatory target of both Cdc28 and the cell wall biosynthesis kinase Cbk1, in a role distinct from its conserved function in cell cycle progression. In stationary phase yeast cells 2D gel electrophoresis shows that there is a diverse pool of Fkh2 phospho-isoforms. For a short window on hyphal induction, far before START in the cell cycle, the phosphorylation profile is transformed before reverting to the yeast profile. This transformation does not occur when stationary phase cells are reinoculated into fresh medium supporting yeast growth. Mass spectrometry and mutational analyses identified residues phosphorylated by Cdc28 and Cbk1. Substitution of these residues with non-phosphorylatable alanine altered the yeast phosphorylation profile and abrogated the characteristic transformation to the hyphal profile. Transcript profiling of the phosphorylation site mutant revealed that the hyphal phosphorylation profile is required for the expression of genes involved in pathogenesis, host interaction and biofilm formation. We confirmed that these changes in gene expression resulted in corresponding defects in pathogenic processes. Furthermore, we identified that Fkh2 interacts with the chromatin modifier Pob3 in a phosphorylation-dependent manner, thereby providing a possible mechanism by which the phosphorylation of Fkh2 regulates its specificity. Thus, we have discovered a novel cell cycle-independent phospho-regulatory event that subverts a key component of the cell cycle machinery to a role in the switch from commensalism to pathogenicity.